2017
DOI: 10.1111/jace.15162
|View full text |Cite
|
Sign up to set email alerts
|

Porcelain stoneware consolidation by flash sintering

Abstract: Porcelain stoneware was consolidated by flash sintering under DC polarization using current densities in the range 4-20 mA/mm 2 . The results show the applicability of this innovative sintering technology to a material whose densification occurs by vitrification, thus allowing to extend the possible application field of flash sintering to traditional ceramics. Using appropriate current density, the flashsintered samples are dense, homogeneous, and well-vitrified. XRD and microstructural analysis points out the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 43 publications
(87 reference statements)
2
53
0
Order By: Relevance
“…It might originate from the localized thermal gradient at the microstructural level. As shown elsewhere, during electric field‐assisted consolidation of insulating materials local overheating or even melting of the grain boundaries occurs. Thus, such temperature gradients in the grain might cause defect redistribution and contribute to explain the larger Sr segregation.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…It might originate from the localized thermal gradient at the microstructural level. As shown elsewhere, during electric field‐assisted consolidation of insulating materials local overheating or even melting of the grain boundaries occurs. Thus, such temperature gradients in the grain might cause defect redistribution and contribute to explain the larger Sr segregation.…”
Section: Resultssupporting
confidence: 52%
“…However, an interaction between the elelctric field/current and the defect chemistry cannot be ruled out. As a matter of fact, field‐induced defect perturbation has been often proposed as the pivotal mechanism for field‐assisted sintering of ceramics …”
Section: Resultsmentioning
confidence: 99%
“…The application of external electric field combined with thermal heat expected to increase the entropy, hence induce amorphicity [47]. Flash experiments of porcelain by Biesuz et al [50] together with fast heating without an electric current confirmed the direct effect of the electric field on softening of the glassy phase at lower temperatures. The effect of rapid sintering due to rapid heating in the absence of electric field [22] was marginal in amorphous porcelain [50].…”
Section: Discussionmentioning
confidence: 90%
“…Many other reports were published applying this technique to other materials [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], studying the dependence on the amplitudes of the electric field and current density [31], on the average particle size [32], on the porosity [33], and searching for an explanation of such events [34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%